Educational Dental Keychains Application in Student Team Achievement Division : Implementation of Dental and Oral Health Promotion - Ika Kusuma Wardani; Deby Kania Tri Putri; Nurul Fitriyani Dewi; Fatma Kirana; Aulia Rahimah; Fatimah Maulideya; Jamilatun Nisa (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2023)
ABSTRACT The implications of effective, efficient, attractive dental and oral health promotion are closely related to a person's level of awareness and behavior in improving the maintenance of oral health and hygiene. The purpose of this community service is to implement the use of Educational Dental Keychains in Student Team Achievement Division as an effort to promote oral health.  The method used 6 steps, they are consisting of conveying goals and motivating students, convey goals and information, motivating students, organizing and guiding students in study groups, evaluating learning outcomes, clarification and feedback by experts and giving awards.: The application of Educational Dental Keychains in the Student Team Achievement Division as an effort to promote dental and oral health has a good influence on students' dental and oral knowledge and a good understanding of students' dental and oral health knowledge. Student knowledge increased descriptively and statistically. The use of Educational Dental Keychains and the STAD health promotion method can be applied as an effort to increase oral and dental health knowledge in children. Keyword: Educational Dental Keychains, health promotion, Student Team Achievement Division, Dental and Oral Health Knowledge, Children